Application of EDAS Method with Entropy Weighting in Performance Assessment of the Best Student Activity Unit - Uswatun Hasanah; Mesran; Rian Syahputra (ADA Research Center, 2024)
The Student Activity Unit (UKM) is an institution formed as a forum for all student activities in developing the interests, talents, creativity and expertise of its members. Performance appraisal is needed to evaluate every achievement and motivate SMEs. Based on the results of interviews conducted with the Vice Chancellor III for Student Affairs at Budi Darma University, he explained that the performance assessment of SMEs at Budi Darma University is still based on the activity of SMEs on campus and has not used other criteria that are clearer and more structured when assessing the performance of the best SMEs at Budi Darma University. . This is certainly less effective and prone to errors. Therefore, a Decision Support System (DSS) is needed as a solution to overcome these problems. In this study, the Entropy method and the EDAS method were applied to 5 criteria and 8 alternatives. Then the alternative chosen according to the criteria for evaluating the performance of the best UKM at Budi Darma University is in alternative A4 with a score of 0.9685, namely SSBD (Sanggar Seni Budi Darma).